The Heterochromatin protein 1 is a regulator in RNA splicing precision deficient in ulcerative colitis - Jorge Mata-Garrido; Yao Xiang; Yunhua Chang-Marchand; Caroline Reisacher; Elisabeth Ageron; Ida Chiara Guerrera; Iñigo Casafont; Aurelia Bruneau; Claire Cherbuy; Xavier Treton; Anne Dumay; Eric Ogier-Denis; et al. (Nature Communications, 2022)
This study reports reduced expression of the chromatin and splicing regulator HP1γ in inflammatory bowel disease (IBD) and shows that HP1γ protects against pervasive RNA splicing leading to toxic mRNA products detected in IBD, like progerin.